Rural Probation Work: Isolation or Autonomy? - John Minkes (Howard Journal, 2013)
This article is based on interviews with probation staff who worked in rural areas in mid-Wales between the 1950s and 1980s. It shows that they enjoyed the autonomy and responsibility that rural work offered. They believed their work had been grounded in traditional probation values and had lessons to offer to probation work as a whole. The article concludes that practice in small communities and non-urban locations can be effective and relevant to practice elsewhere.